Clinics in diagnostic imaging (62). Gallstones with acute cholecystitis. - Muttarak M. (2014)
A 75-year-old man presented with right upper quadrant pain and fever. Ultrasonography showed gallstones, gallbladder enlargement, gallbladder wall thickening and pericholecystic fluid collection. Cholecystectomy confirmed the diagnosis of acute cholecystitis. The differential diagnosis of right upper quadrant abdominal pain and fever is discussed, and the role of imaging in its evaluation is emphasised.